IT Management And Its Roles In Creating High Performance SME Within Marine Industry In Malaysia & France - Abdullah, Saliza (2003)
The research paper will address the roles of IT Management in facilitating the interactions of three major forces - innovation, strategy and change to create high performance small and medium enterprises(SME) within marine industry in Malaysia and France.